2016
DOI: 10.1002/2015jb012633
|View full text |Cite
|
Sign up to set email alerts
|

Fault structure, stress, or pressure control of the seismicity in shale? Insights from a controlled experiment of fluid‐induced fault reactivation

Abstract: Clay formations are present in reservoirs and earthquake faults, but questions remain on their mechanical behavior, as they can vary from ductile (aseismic) to brittle (seismic). An experiment, at a scale of 10 m, aims to reactivate a natural fault by fluid pressure in shale materials. The injection area was surrounded by a dense monitoring network comprising pressure, deformation, and seismicity sensors, in a well‐characterized geological setting. Thirty‐two microseismic events were recorded during several in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 60 publications
(89 reference statements)
6
63
0
Order By: Relevance
“…The same pattern was observed in the Mayet de la Montagne experiments (Scotti & Cornet, ) where water injections in a 800 m long borehole mainly drove aseismic deformation. Aseismic motion was also observed in controlled in situ fluid injection experiments at meter scale in limestone (Guglielmi et al, ) or in shale (De Barros et al, ). At the laboratory scale, Goodfellow et al () performed fluid injection experiments on granite samples under triaxial stresses and showed that most of the deformation is aseismic during the fluid pressurization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same pattern was observed in the Mayet de la Montagne experiments (Scotti & Cornet, ) where water injections in a 800 m long borehole mainly drove aseismic deformation. Aseismic motion was also observed in controlled in situ fluid injection experiments at meter scale in limestone (Guglielmi et al, ) or in shale (De Barros et al, ). At the laboratory scale, Goodfellow et al () performed fluid injection experiments on granite samples under triaxial stresses and showed that most of the deformation is aseismic during the fluid pressurization.…”
Section: Introductionmentioning
confidence: 99%
“…Other processes triggering seismicity can be fracture propagation through hydrofracturing (Cornet, ) and poroelastic stress perturbation transferred through failure away from a pressure source (Goebel et al, ). Nevertheless, recent observations (De Barros et al, ; Guglielmi et al, ; Zoback et al, ) showed that fluid pressure first drives an aseismic fault rupture. The seismicity appears as a secondary process and a response of the surrounding medium to the aseismic rupture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of phyllosilicate minerals strongly reduces the frictional strength of faults [Ikari et al, 2009;Faulkner et al, 2011;Kohli and Zoback, 2013]. Several factors can explain this situation: (1) the failure of shales is complex due to the dependences of their mechanical properties to the mineralogy and the water content [Ikari et al, 2009;Kohli and Zoback, 2013;De Barros et al, 2016] and (2) laboratory experiments on shales are not fully representative of this complex behavior. However, assessing deformation and failure processes in shales is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Armed with new technology in fault zone drilling and geodesy, a new-generation earthquake experiment could more directly measure fault slip and fluid pressures within both the fault core as well as the surrounding damage zone, which should enhance our ability to determine where and when failure will occur. Recent borehole experiments have successfully induced small earthquakes (−4.5<M w < − 3) in a controlled way (Derode et al, 2015;Guglielmi et al, 2015;De Barros et al, 2016). Observations of the induced earthquakes have demonstrated that the physical processes that lead to runaway slip are complex and depend on the hydromechanical and frictional characteristics of both the fault and the surrounding rock.…”
Section: Knowledge Gaps Between Earthquake Theory and Observationmentioning
confidence: 99%